2018
DOI: 10.1111/imm.12893
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of lovastatin and AMP‐activated protein kinase activator improves mitochondrial and peroxisomal functions and clinical disease in experimental autoimmune encephalomyelitis model

Abstract: Recent studies report that loss and dysfunction of mitochondria and peroxisomes contribute to the myelin and axonal damage in multiple sclerosis (MS). In this study, we investigated the efficacy of a combination of lovastatin and AMP-activated protein kinase (AMPK) activator (AICAR) on the loss and dysfunction of mitochondria and peroxisomes and myelin and axonal damage in spinal cords, relative to the clinical disease symptoms, using a mouse model of experimental autoimmune encephalomyelitis (EAE, a model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 80 publications
(250 reference statements)
0
28
0
Order By: Relevance
“…A combined administration of the statin lovastatin and AICAR to autoimmune encephalomyelitis mice alleviated inflammation-induced dysfunction of mitochondria and peroxisomes as well as demyelination. Thus, restoring peroxisome function might be beneficial for MS disease prognosis (Singh et al 2018 ).…”
Section: News From the Brain: Unravelling The Mysterious Role Of Peromentioning
confidence: 99%
“…A combined administration of the statin lovastatin and AICAR to autoimmune encephalomyelitis mice alleviated inflammation-induced dysfunction of mitochondria and peroxisomes as well as demyelination. Thus, restoring peroxisome function might be beneficial for MS disease prognosis (Singh et al 2018 ).…”
Section: News From the Brain: Unravelling The Mysterious Role Of Peromentioning
confidence: 99%
“…9 The study also reported that the metabolite mevalonate is the mediator of training through activation of insulin-like growth factor 1 receptor and mammalian target of rapamycin and subsequent histone modifications in inflammatory pathways. 9 Consistent with a role of statins in immune metabolism, another study reported that lovastatin caused potent protection against inflammationinduced loss and dysfunction of mitochondria and peroxisomes in a mouse model of MS. 10 These different approaches show that statins affect the immune response on multiple layers including signalling, gene transcription, epigenetic modifications and immune metabolism.…”
Section: Mechanisms Of Actions Of Statins On Different Immune Cellsmentioning
confidence: 99%
“…The preclinical studies demonstrated that the combination of lovastatin and AICAR in therapy improved neuroprotection against inflammatory mediators-induced dysfunction in mitochondria and peroxisomes in EAE model [ 74 ]. Furthermore, there is evidence that the supplementation of AICAR with statin combination treatment may provide greater efficacy for MS than statin alone [ 75 ]. Due to insufficient molecular and clinical studies of metformin properties in MS, its effectiveness cannot be unambiguously established.…”
Section: Overview Of the Favourable Cellular Effects Of Using Metfmentioning
confidence: 99%